The Criminal Manipulation in Government Medical Statistics During COVID-19 Crisis: A Comparative Study - Dhia Moslem Abd Alameer Ghaibi; Asseel Abd Ali Shehad (Indian Journal of Forensic Medicine & Toxicology, 2021)
Manipulating government medical data is one of the intentional crimes that occur on medical informationaldata, whether by intentionally introducing misleading and wrong information or deleting and amendingthe data to change the truth. Despite the existence of laws to criminalize these acts, whether in Iraqi lawor comparative law in general, in addition to the international conventions that oblige countries to developlegal texts to combat cybercrimes. Therefore, there are problems related to the activation of texts associatedwith manipulating government medical data, especially data on infection with Coronavirus. Providing somecountries with misleading or incorrect information that does not reflect the current reality must be put to anend, especially since this disease is a fatal and dangerous disease that transmits very quickly and must beaccurately determined without any tampering with the governmental medical data.